The Impact Of Smartphones In Enhancing Writing Skills On Kurdish Efl University Students - Hemn Mohammed Ali Mahmood; Zanyar Nathir Ghafar; Chro Omer Sdiq; Asuda Faraj Muhialdeen; Shanga Sleman Mohammed (Journal Of Social Science (JoSS), 2024)
Smartphones have become an important Internet platform and play an essential role in individuals' daily lives, and their use is gaining popularity due to their various features. The study's main objective was to investigate the potential of smartphones as tools for improving English writing skills. The proliferation of Education has facilitated the broad adoption of mobile language learning, prompting this research to examine the growing inclination of undergraduate students to acquire English language skills via the use of Smartphones. The quantitative method was used to collect data by conducting a questionnaire to undergraduate students, and the survey included the recruitment of 52 individuals, with ages ranging from 18 to 23; among all those who took part, there were 41 females and 11 males. The results indicated that using smartphones positively impacted various aspects of English language proficiency, such as listening, reading, writing, grammar, vocabulary, pronunciation, and communication. The findings show that the respondents acknowledged the benefits of employing social media and smartphones to enhance their writing abilities by using smartphones, and this pattern is anticipated to persist in the forthcoming period.